Crafting Loyalty: How Social, Seductive, and Recreational Experiences Shape Mall-Goers' Fidelity Through Visitor Satisfaction - Oktaviani, Elma (Open Access Indonesia Journal of Social Sciences, 2024)
This research aims to analyze the influence of social experience, seductive experience, and recreational experience on mall visitor loyalty which is mediated by visitor satisfaction. This type of research is descriptive research with the research population being Indonesian citizens and 100 respondents were obtained through a sampling technique, namely purposive sampling with criteria (they are Indonesian citizens who come from one of the regions in Java: Jakarta, West Java, Central Java, East Java, and Yogyakarta 2). Have visited the mall in their area at least once. The data analysis technique used in this research is PLS (partial least squares) and from the results of data analysis it is found that social experience and visitor satisfaction partially have a positive influence on visitor loyalty, seductive experience and recreational experience partially have no effect on mall visitor loyalty. Visitor satisfaction can mediate the influence of social experience on mall visitor loyalty, but is unable to partially mediate seductive experience and recreational experience on mall visitor loyalty.